Intelligence Report on Bambuko Clan, Kumba Division, Cameroons Province (Colonial Letters and the Contact of Knowledges, 1935)
This file contains colonial intelligence report on Bambuko Clan, Kumba Division, Cameroons Province
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies